The Dynamics of Globalization and Local Cultural Identity: Challenges, Opportunities, and the Role of Digital Technology in Cultural Preservation - Zulkarnain, Muhamad Amir Bin (Bulletin of Science, Technology and Society, 2024)
Globalization has brought significant changes to local cultural identity, both in the form of challenges and opportunities. This study aims to analyze the impact of globalization on the preservation of local culture and the role of digital technology in strengthening or weakening cultural identity in modern society. This literature review examines various findings from reputable international journals to understand the dynamics of interaction between local and global cultures. The results of the study show that globalization can accelerate the erosion of local culture due to the dominance of a stronger global culture through the mass media, lifestyle, and increasingly uniform social values. The loss of local languages, the decline in traditional cultural practices, and changes in the education system that do not emphasize the importance of local cultural identity are major challenges in cultural preservation. However, globalization also opens up opportunities for cultural revitalization through localization strategies, digital nationalism, and the use of digital technology to document and disseminate local cultural heritage. The use of social media, digital platforms, and virtual reality technology has proven effective in increasing the awareness and involvement of the younger generation in local culture. Therefore, this study emphasizes the importance of policy strategies that support cultural preservation by utilizing technology as the main tool to maintain cultural heritage in the midst of increasingly strong globalization.